2017
DOI: 10.3389/fnbeh.2017.00128
|View full text |Cite
|
Sign up to set email alerts
|

Reward Draws the Eye, Uncertainty Holds the Eye: Associative Learning Modulates Distractor Interference in Visual Search

Abstract: Stimuli in our sensory environment differ with respect to their physical salience but moreover may acquire motivational salience by association with reward. If we repeatedly observed that reward is available in the context of a particular cue but absent in the context of another cue the former typically attracts more attention than the latter. However, we also may encounter cues uncorrelated with reward. A cue with 50% reward contingency may induce an average reward expectancy but at the same time induces high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
7
33
1
Order By: Relevance
“…An aversive learning experiment found that the trial‐by‐trial PSR predominantly reflects expected CS outcome (Tzovara et al, ). Interestingly, earlier studies have also found evidence in support of the Pearce‐Hall learning theory in gaze‐dwelling time, showing longer gaze durations on stimuli associated with appetitive and aversive uncertain outcome (Hogarth, Dickinson, Austin, Brown, & Duka, ; Koenig, Kadel, Uengoer, Schubö, & Lachnit, ), which is consistent with our result. Taken together, while pupil dilation was a sensitive measure of appetitive conditioning in our study, it seems to be more related to attentional processes rather than appetitive value.…”
Section: Discussionsupporting
confidence: 93%
“…An aversive learning experiment found that the trial‐by‐trial PSR predominantly reflects expected CS outcome (Tzovara et al, ). Interestingly, earlier studies have also found evidence in support of the Pearce‐Hall learning theory in gaze‐dwelling time, showing longer gaze durations on stimuli associated with appetitive and aversive uncertain outcome (Hogarth, Dickinson, Austin, Brown, & Duka, ; Koenig, Kadel, Uengoer, Schubö, & Lachnit, ), which is consistent with our result. Taken together, while pupil dilation was a sensitive measure of appetitive conditioning in our study, it seems to be more related to attentional processes rather than appetitive value.…”
Section: Discussionsupporting
confidence: 93%
“…In short, the theory predicts that, after learning the reward contingencies, partially reinforced, uncertain cues (50% reinforcement, high prediction error) attract more attention than consistently reinforced cues (100% reinforcement, small prediction error). Empirical evidence in support of this hypothesis has been previously reported for classical conditioning in rats (Haselgrove, Esber, Pearce, & Jones, 2010;Kaye & Pearce, 1984;Swan & Pearce, 1988) and with respect to longer fixation dwell time on uncertain cues in human associative learning (Hogarth, Dickinson, Austin, Brown, & Duka, 2008;Koenig, Kadel, Uengoer, Schub€ o, & Lachnit, 2017;.…”
Section: Introductionsupporting
confidence: 68%
“…In the human domain, an attentional bias for uncertain cues has been reported with respect to total dwell time during learning (Beesley, Nguyen, Pearson, & Le Pelley, ; Hogarth et al, ). Additionally, it has recently been demonstrated that such an overt selection bias for uncertain cues is automatic to some extent and prolongs fixation duration on previously uncertain cues, even if these cues are introduced as irrelevant distracters in a different task where any selection of these distracters is nonstrategic and counterproductive (Koenig, Kadel et al, ; Koenig, Uengoer, & Lachnit, ). In extension of these previous findings, our results provide evidence for the unique prediction of how attentional priority should change from the outset to the end of training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations